UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF DAN MINAT BELAJAR SISWA MENGGUNAKAN MODUL BERBASIS SCIENTIFIC APPROACH KELAS VII C SMP NEGERI 4 SURAKARTA - Wulandari, Puspita Septim; Raharjo, Thrustho; Harjunowibowo, Dewanto (Physics Education Department, Faculty of Teacher Training and Education, UNS, 2015)
The objectives of this research are: (1) to improve the studentsâ cognitif competence of 7th grade students of SMPN 4 Surakarta in the second semester, 2014/2015 academic year particulary in temperature, heat and heat transfer material by using scientific approach-based modul, and (2) to improve the learning interest.This Classroom Action Research (CAR) adopts Kurt Lewin model. It was conducted collaboratively between the researcher and the teacher within two cycles. Each cycle began with preparation stage then followed by implementation of using the modul within the cycle stage which covers planning, action, observing, and reflection stage. The subject of the research was 33 students at the 7th grade in SMPN 4 Surakarta in the 2014/2015 academic year. The research was particularly conducted to teach temperature, heat and heat transfer material. The data were collected through observation, interview with teacher and students, post test, questionnaire, and document analysis. The data were validated through triangulation technique. The data analysis employed used qualitative and quantitative technique.The finding of this research shows that: (1) The studentsâ cognitive competence improved as much as 2,73% surpassing the expected target. The number of students who met the passing grade was 72,73%, with the passing score of 86. (2) the studentsâs learning interest also improved as much as 2,5% surpassing the expected target. The aspects of learning interest that became the focus of this research improved such as: (1) the willingness which improved to 82,89%, (2) the attention which improved to 76,08%, (3) and the participation which improved to 78,57%.Kata kunci : cocnitive competence, learninginterest, instructional modul, scientific approach